Electrical technology - Subramaniam, N. P.; Mathew,Anoop (New Delhi: Narosa Publishing House, 2017)
ELECTRICAL TECHNOLOGY is systematically developed to meet the syllabus of undergraduate course in Electrical Engineering of various universities. The complicated concepts are explained in a lucid manner with the help of necessary diagrams and waveforms. Comprehensive coverage has been made to explain the concepts of application-level topics like Electric Traction and Power Electronics. Review questions have been added at the end of each chapter for better understanding of the subject apart from numerous numerical and design problems.
Includes references
Keywords: Electric engineering -- Electric circuits -- Electric machinery -- Electronics